2019
DOI: 10.1055/a-0998-8234
|View full text |Cite
|
Sign up to set email alerts
|

Patient Expectations about Communication in the Perioperative Setting of Elective Knee Surgery – a Questionnaire-based Cross-sectional Study

Abstract: Background Patient expectations are an issue which is attracting increased interest in outcome research for knee surgery procedures. So far, research into patient expectations has mainly focused on the procedure and postoperative functional improvements. The purpose of this study was to identify patient expectations in the perioperative setting. Material and Methods This was a single-center prospective study. A 17-item questionnaire (ordinal answer scale) about patientsʼ perioperative expectations wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The authors concluded this demonstrated a large desire for patients to have direct access to their surgeon. A recent study surveying expectations of communication during the perioperative period of joint-sparing elective knee surgery reported that 63% of patients felt it "important" or "very important" that the operating surgeon was available by phone after surgery compared to only 32% feeling "important" or "very important" of surgeon email availability [14]. Further, when surveying 310 patients in an urban academic orthopaedic practice regarding preferences for an orthopaedic smartphone app, Datillo et al found that the ability to communicate with the physician team was one of the most desired features, just trailing appointment reminders and the access to test or procedure results [12].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded this demonstrated a large desire for patients to have direct access to their surgeon. A recent study surveying expectations of communication during the perioperative period of joint-sparing elective knee surgery reported that 63% of patients felt it "important" or "very important" that the operating surgeon was available by phone after surgery compared to only 32% feeling "important" or "very important" of surgeon email availability [14]. Further, when surveying 310 patients in an urban academic orthopaedic practice regarding preferences for an orthopaedic smartphone app, Datillo et al found that the ability to communicate with the physician team was one of the most desired features, just trailing appointment reminders and the access to test or procedure results [12].…”
Section: Discussionmentioning
confidence: 99%